Surveying marine biodiversity using eDNA metabarcoding of seawater and sediment in a high Arctic fjord during the polar night (Kongsfjorden, Svalbard) - Ayla Murray; Adria Antich; Annkathrin Dischereit; Luisa Düsedau; Clara J.M. Hoppe; Charlotte Havermans (Marine Environmental Research, 2025)

DNA metabarcoding reveals a diverse, omnivorous diet of Arctic amphipods during the polar night, with jellyfish and fish as major prey - Annkathrin Dischereit; Jan Beermann; Benoit Lebreton; Owen S. Wangensteen; Stefan Neuhaus; Charlotte Havermans (Frontiers in Marine Science, 2024)
Introduction Currently, Arctic marine ecosystems are witnessing the most rapid physical changes worldwide, leading to shifts in pelagic and benthic communities and food web structure, concomitant with the introduction of boreal species. Gelatinous zooplankton or jellyfish represent one particular group of which several boreal species are prone to undergo significant poleward range expansions and population increases in the Arctic in the course of the ongoing changes. Historically, jellyfish were considered a trophic dead-end, but an increasing number of studies using modern tools have highlighted their role as major prey items in marine food webs. In this study, we aimed to verify the role of jellyfish and other metazoans as food sources in the Arctic polar night food web, when pelagic resources are limited. Methods We identified the diet of different bentho-pelagic amphipod species in the Atlantifying Kongsfjorden (West Svalbard) during the polar night. We regularly sampled lysianassoid and gammarid amphipods using baited traps and hand nets over a period of one month during the polar night and identified their diet spectrum by applying DNA metabarcoding (COI) to their stomach contents. Results We demonstrate that all investigated species are omnivorous. Fish species including polar cod and snailfish, likely in the shape of carrion, played an important role in the diet of the scavengers Orchomenella minuta and Anonyx sarsi . Predation and potential scavenging on jellyfish contributed to the diet of all four investigated species, particularly for the species Gammarus setosus and G. oceanicus , as evidenced by high read abundances and high frequencies of occurrence. Besides jellyfish, crustaceans and macroalgae were important components of the diet of the two Gammarus species. Discussion The diverse jellyfish community present in Kongsfjorden in the polar night is clearly being utilized as a food source, either through pelagic feeding or feeding on jelly-falls, albeit to a different extent in the local amphipod community. These findings provide novel insights into the Arctic food web during the polar night and represent the first evidence of feeding on natural (non-experimental) jelly-falls.